Disruption of cyclooxygenase type 2 exacerbates apoptosis and renal damage during obstructive nephropathy - Nilsson, Line (Am J Physiol Renal Physiol, 2015)
Renal oxidative stress is increased in response to ureteral obstruction. In vitro, cyclooxygenase (COX)-2 activity contributes to protection against oxidants. In the present study, we tested the hypothesis that COX-2 activity counters oxidative stress and apoptosis in an in vivo model of obstructive nephropathy. Renal oxidative stress markers, antioxidant enzymes, and markers of tubular injury, tubular dilation, and apoptosis were investigated in COX-2 knockout (COX-2(−/−)) and wild-type (WT) mice subjected to 3 or 7 days of unilateral ureteral obstruction (UUO). In a separate series, WT sham-operated and UUO mice were treated with a selective COX-2 inhibitor, parecoxib. COX-2 increased in response to UUO; the oxidative stress markers 4-hydroxynonenal and nitrotyrosine protein residues increased in kidney tissue with no genotype difference after UUO, whereas the antioxidant enzymes heme oxygenase-1 and SOD2 displayed higher levels in COX-2(−/−) mice. Tubular injury was aggravated by COX-2 deletion, as measured by tubular dilatation, an increase in kidney injury molecule-1, cortical caspase-3 content, and apoptosis index. In conclusion, COX-2 is necessary to protect against tubular injury and apoptosis after UUO but not necessary to protect against oxidative stress. COX-2 is not likely to directly regulate antioxidant enzymes heme oxygenase-1 and SOD in the kidney.